Hapusnya Hak Mewaris Para Ahli Waris Menurut Pasal 838 KUHPERDATA - Asep Irfan; Siah Khosyi’ah (Yayasan Cendekia Gagayunan Indonesia, 2024)
The purpose of this research is to find out how the regulation of Inheritance Law according to the Civil Code and how the elimination of inheritance rights and its legal consequences for the heirs. By using normative juridical research methods, it is concluded: 1. Although the heirs in inheritance law are guaranteed the right to inherit as an absolute part (legitieme portie), but in certain cases and circumstances, the heirs' inheritance rights can be revoked or nullified, among others, due to committing crimes such as persecution of the testator, forgery of wills, and so forth. 2. The legal consequences of the elimination of the right to inherit, among others, are that the heirs concerned, in addition to not being entitled to inheritance, can be ostracized or excluded as members of the extended family of the testator.